Education and Social Cohesion in Latin America: a micro-political Perspective - Gvirtz, Silvina; Beech, Jason (Education Policy Analysis Archives, 2014)
This article analyses the relation between education and social cohesion in Latin America from a micropolitical perspective. Even though we acknowledge the relevance of the macro and mezzo levels, we argue that the political decisions that are made at the school level are crucial to understand the contribution of educational systems to social cohesion. We suggest that the relation between social cohesion and school micropolitics can be analysed in two dimensions: the first is related to the access and permanence of children in school, while the second is related to the curriculum. The article concentrates on the second level by analysing the relation between the curriculum and social cohesion from a local, a national, and a global perspective.